2013
DOI: 10.1016/j.jpainsymman.2012.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Decisional Control Preferences of Hispanic Patients With Advanced Cancer From the United States and Latin America

Abstract: HUSs had more active DCPs than HLAs did. Among HUSs, acculturation did not seem to play a role in DCP determination. Our findings confirm the importance of family participation for both HUSs and HLAs. However, HUSs were less likely to want family members to make decisions on their behalf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 27 publications
1
42
0
1
Order By: Relevance
“…17,38 In a meta-analysis of end-of-life decision making among racially and ethnically diverse groups, Kwak and Haley found that Korean and Mexican Americans, regardless of acculturation status, were more likely to designate a family member as the primary medical decision maker. 39 However, other studies found no association between DCPs and minority status or acculturation to the U.S. 13,16 Regardless, it is important to elicit and honor different views concerning DCPs because the value of autonomy in decision making is often culturally and contextually dependent. 37,38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,38 In a meta-analysis of end-of-life decision making among racially and ethnically diverse groups, Kwak and Haley found that Korean and Mexican Americans, regardless of acculturation status, were more likely to designate a family member as the primary medical decision maker. 39 However, other studies found no association between DCPs and minority status or acculturation to the U.S. 13,16 Regardless, it is important to elicit and honor different views concerning DCPs because the value of autonomy in decision making is often culturally and contextually dependent. 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…Patients who are more passive within clinical encounters, particularly minorities, are less likely to receive information from clinicians. 12,13,22-25 These patients also tend to report lower satisfaction with communication. 20-23 …”
Section: Introductionmentioning
confidence: 99%
“…In a previous article, we reported that Hispanics from the U.S. had more active DCPs than Hispanics from Latin America. 12 The objective of this paper was to report our findings regarding the association between DCPs, sociodemographic and clinical characteristics, and Hispanic patients’ preferences for disclosure of diagnostic and prognostic information. We also determined the concordance between patients’ DCPs and their self-reported DCPs related to their cancer care and identified the factors that influence patient satisfaction with the decision control process.…”
Section: Introductionmentioning
confidence: 99%
“…However, several researchers have observed passive attitudes toward decision-making among cancer patients; in fact, a recent research review has shown that passive attitudes remain dominant in patients 3 . Although many researchers accept the importance of shared attitudes in decision-making, these observations might be caused by differences in patient ethnicity, age 4,5 , and background experience 6 . According to a recent study, patients prefer to be controlled by the physician in decision-making; they trust their physician 7 .…”
Section: Introductionmentioning
confidence: 99%